The influence of different rootstocks and the sampling method in macronutrients concentration in leaves of Satsuma mandarin trees (Citrus unshiu, Marc.) - Creste, José Eduardo; de Lima, Leonia Aparecida (Pesquisa Agropecuaria Brasileira, 1995)
The influence of three different rootstocks and the sampling method in the nitrogen, phosphorus, potassium, calcium, magnesium and sulphur concentration in leaves of "Owari" Satsuma mandarins trees (Citrus unshiu, Marc.) were investigated through leaf analysis. The three rootstocks studied were: Rangpur lime (Citrus limon (L.) Osbeck), Sunki mandarin (Citrus sunki Hort ex-Tanaka) and Cleopatra mandarin (Citrus resnhi Hort ex-Tanaka). The leaf samples were taken from nonfruiting and fruiting branches of spring growth cycle. The results showed no significant influences of the different rootstocks in the macronutrients concentration in two types of branches; the N, P and K concentrations were significantly larger in the nonfruiting branches, and Ca concentration significantly larger in the fruiting branches. No difference was found in the Mg and S content in the two types of branches.
Keywords: citrus; leaf analysis; mineral nutrition